Research on the Role of Accounting Information Disclosure and Corporate Governance Structure in Protecting Shareholders' Rights and Interests - Bian, Wenjie (Transactions on Economics, Business and Management Research, 2024)
The influence of accounting information disclosure and corporate governance structure on the protection of shareholders' rights and interests is a complex and key research topic. This paper discusses how accounting information disclosure and corporate governance structure work together to protect shareholders' rights and interests, aiming at revealing its internal mechanism and influence path. It is found that high-quality accounting information disclosure and optimized corporate governance structure can significantly enhance the protection of shareholders' rights and interests. First of all, transparent disclosure of accounting information helps shareholders to understand the financial situation and operating performance of enterprises, so as to make wise investment decisions. Secondly, an effective corporate governance structure can restrict the self-interest behavior of management, reduce the risk of insider control and further protect the rights and interests of shareholders. Therefore, for enterprises, it is very important to constantly improve the accounting information disclosure system and optimize the governance structure, which not only helps to enhance the overall value of enterprises, but also strengthens the trust and loyalty of shareholders to enterprises.